Electrical conductivity and dielectric constant of geopolymer cement mortar. Issue 2 (20th April 2018) - Saxena, Sunil K; Kumar, Mukesh; Singh, Nakshatra B
Abstract : In the last few decades, increasing efforts have been made towards the utilization of fly ash, especially in an efficient and green fashion. The geopolymer technology provides a green solution to the utilization of fly ash, avoiding its negative impact on environment and ecology. Geopolymer cement was made by activating pond fly ash with 14 M sodium hydroxide (NaOH) and sodium silicate solutions. Natural sand was used to make the mortar. Alccofine powder, a substitute of silica fume, was also added during the geopolymerization process. Curing was done at 80°C for 12 h. It is reported that geopolymer possess high electrical conductivity at room temperature which can play an important role in fast ionic conduction used for solid-state batteries and other solid-state electrochemical devices. In this paper, electrical conductivity and dielectric constant, compressive strength and scanning electron microscopy studies were done to characterize the geopolymer. The energy of the activation for conduction was found to increase with frequency. The results are discussed.